If the value of the series above can be expressed as where are positive integers, and are coprime to each other, find the value of .
See Also Inverse Sum and Inverse Sum Squared .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note first that k = 0 ∑ n k 3 = ( 2 n ( n + 1 ) ) 2 . So the given sum can be expressed as
4 n = 1 ∑ ∞ ( n ( n + 1 ) 1 ) 2 = 4 n = 1 ∑ ∞ ( n 1 − n + 1 1 ) 2 = 4 n = 1 ∑ ∞ ( n 2 1 + ( n + 1 ) 2 1 − n ( n + 1 ) 2 ) =
4 ( 2 n = 1 ∑ ∞ ( n 2 1 ) − 1 ) − 8 n = 1 ∑ ∞ ( n 1 − n + 1 1 ) = 4 ∗ ( 6 2 π 2 − 1 ) − 8 ∗ 1 = 3 4 π 2 − 1 2 .
Thus a + b + c = 4 + 3 + 1 2 = 1 9 .
Note that n = 1 ∑ ∞ n 2 1 = 6 π 2 is the solution to the Basel problem , and n = 1 ∑ ∞ ( n 1 − n + 1 1 ) is a telescoping sum where all the terms cancel pairwise except the very first, namely 1 1 = 1 .